Cross-Cultural Education Model Through Multicultural Classrooms : An Ethnographic Study in Secondary Schools - Maulani, Hikmah; Erihadiana, Mohamad; Ruswandi, Uus (Jurnal Paedagogy, 2025)
This study aims to analyze the implementation of cross-cultural reflection within the context of multicultural education, focusing on understanding the dynamics of cultural diversity in the classroom. This research uses an ethnographic method with a qualitative approach. The research data were obtained through participant observation, in-depth interviews, and document analysis in several multicultural schools in Indonesia. Data analysis Involves identifying recurring themes, patterns, and ideas within the data, process of comparing data segments to identify similarities and differences, focuses on the stories and experiences shared by participants. The findings indicate that cross-cultural education plays an important role in improving intercultural understanding, motivating students, and creating a more inclusive learning environment. The integration of local culture into learning through the use of folklore and traditional practices has proven effective in increasing student engagement. In addition, the results of the study reveal the need for further training for teachers in adopting an ethnopedagogical approach to overcome learning barriers due to cultural differences.